Psychodynamic therapy for non-compliance: a case report. (June 2019) - Saha, Shanthi; McCarthy, Claire; Dhillon, Rohan
Objectives: This paper outlines the use of psychodynamic psychotherapy as an adjunct to treatment as usual for addressing challenging behaviours in a patient with schizophrenia under the care of a community mental health team (CMHT) in South Australia. Methods: Ms P suffered from schizophrenia and demonstrated challenging behaviours in the context of being administered depot medication under a community treatment order (CTO). Multiple attempts at addressing non-compliance and consistently disruptive behaviour through conventional methods had failed. Consequently, the novel approach of fortnightly psychodynamic psychotherapy sessions was trialled for 5 months, augmenting treatment as usual. Results: Psychodynamic psychotherapy proved effective for this patient. With treatment, she showed an improved compliance and overall engagement. Additionally, consequent to regularly receiving medication, her mental state improved and hospitalisations decreased. Conclusions: Further research could lead to a better understanding of how and in what contexts, psychodynamic therapy and psychodynamic thinking can be utilised in the public health system.